Caracterización de los árboles monumentales en los senderos del Cuyabeno River Lodge Ciudad - Toro Guerrero, Estefany Graciela (2018)
The project was carried out in the Cuyabeno River Lodge, which is located in the Cuyabeno Faunal Production Reserve with a minimum temperature of 23ºC, which is made up of communities such as Siona, Quichua, Secoya, Shuar and Cofán, which contribute to the community tourism. The project was developed based on the main problem, which has been identified that in the Lodge there are no investigations carried out regarding the Environmental area on the Monumental trees existing on the site. To this end, a guide was prepared based on a diagnosis, which allowed to know the initial state of the area, and which are the most representative tree species, which For the recognition of the area and registration, the path was defined with the help of the Rapid Ecological Evaluation Sheet, it should be noted that for the exploration of ancestral knowledge, it was recorded in personalized files, through interviews with key persons, while for the Taxonomic classification was used to take photographs of the species and to obtain the distribution map bibliographies were used in the same way to know the conservation status of each species found on the site. The methodology that was used in the present project is a mixed methodology since the quantitative and qualitative method was used, which implies techniques that are field, interview and bibliographic, in this way relevance and reliability were obtained in the obtained data. Finally, all the information collected was systematized in the design of the guide, which contributes both to nature and to the human being, as a tool for environmental and cultural conservation.